Living Labs and the DH Centre: Lessons for Each from the Other - Ferronato, Priscilla; Mercer, Lisa; Roberts-Smith, Jennifer; Ruecker, Stan (KULA, 2019)
The digital humanities (DH) has a long and successful history of creating, using, and maintaining DH centres, as evidenced by the vast centerNet network. Furthermore, some of the most successful centres are constantly evolving in form and function. In this paper, we propose that the next phase in the evolution of the DH centre may involve a related phenomenon from the design research community, called the ‘Living Lab.’ The European Network of Living Labs describes them as dedicated to open forms of design for social good: ‘Living Labs (LLs) are defined as user-centred, open innovation ecosystems based on a systematic user co-creation approach, integrating research and innovation processes in real-life communities and settings.’ Current member labs deal with topics ranging from health and well-being (52%) to mobility (14%), but there are few that focus on issues central to DH, such as open social scholarship. We argue that incorporating more DH into the Living Labs network, and more Living Labs into DH centres, would benefit everyone involved. Specifically, DH labs could benefit from Living Labs’ experience with complex problems, and Living Labs could benefit from DH centres’ experience producing research.